2022
DOI: 10.1101/2022.09.17.508207
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proteogenomic analysis reveals RNA as an important source for tumor-agnostic neoantigen identification correlating with T-cell infiltration

Abstract: Systemic pan-tumor analyses may reveal the significance of common features implicated in cancer immunogenicity and patient survival. Here, we provide a comprehensive multi-omics data set for 32 patients across 25 tumor types by combining proteogenomics with phenotypic and functional analyses. By using an optimized computational approach, we discovered a large number of novel tumor-specific and tumor-associated antigens including shared common target candidates. To create a pipeline for the identification of ne… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
2
3
0
Order By: Relevance
“…Our analysis of tumor variants using DNAseq and RNAseq data obtained from 25 CRC patients identified a moderate proportion (22.4%) of shared somatic variants (Figure 2A). This finding is consistent with a previous study that reported a similar trend in two datasets (58).…”
Section: Discussionsupporting
confidence: 94%
“…Our analysis of tumor variants using DNAseq and RNAseq data obtained from 25 CRC patients identified a moderate proportion (22.4%) of shared somatic variants (Figure 2A). This finding is consistent with a previous study that reported a similar trend in two datasets (58).…”
Section: Discussionsupporting
confidence: 94%
“…Our analysis of tumor variants using DNAseq and RNAseq data obtained from 25 CRC patients identified a moderate proportion (22.4%) of shared somatic variants ( Figure 2A ). This finding is consistent with a previous study that reported a similar trend in two datasets ( 59 ). The differences in variants identified by DNAseq and RNAseq could be attributed to variations in sequencing technologies or variant calling tools, as reported in previous studies ( 60 ).…”
Section: Discussionsupporting
confidence: 94%
“…This rescoring approach has been already found useful in large-scale proteomic experiments as well as in confirming neoantigen (genometranslated or variant database) identifications. 42,55,56 Finally, confidence levels for SSPPs were established by assessing their species-level specificity within UniProt and RefSeq proteomes. Later, these peptides were categorized into high, medium, low, and poor confidence based on stringent SA and Abs.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Later, the experimental and predicted peptide spectra for each peptide precursor of a species were subjected to pairwise spectral comparison for calculation of normalized spectral contrast angle (SA). 40,42 Orbitrap (FTMS) and Ion Trap (ITMS) derived fragment spectra (MS/MS) were matched to HCD and collision-induced dissociation (CID) model derived predicted spectra with 20 ppm and 0.5 Da match tolerance using in-house Python script (https://github.com/chinmayaNK22/ SpecAngle), respectively. The retention time difference between the experimental and predicted spectra of each peptide precursor was calculated as a further substantiation factor.…”
Section: Ntm Strains and Culturesmentioning
confidence: 99%
See 1 more Smart Citation